Barn som gikk «fra haand til haand» - Bugge Dystland, Ingrid; Haave, Per; Messel, Jan; Norburg, Ulrika; Åse Reitan, Aud; Reitan, Jon; Sem, Leiv; Gunn Slottemo, Hilde; Neerland Soleim, Marianne; Sundkvist, Maria; Teige, Elisabeth; Thuen, Harald; et al. (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2024)
Orphanages and similar institutions were established in Norway in the latter part of the 19th century. The new practice of moving children from their homes to an institution was part of a new and comprehensive public welfare system and a consequence of new laws regarding compulsory schooling. The institutions drew inspiration and ideas from other European countries. The institutions – special schools, boarding schools, and those run by the public child-protection authorites – were each established for different reasons and with different justifications. Some were both home and school, while at others, the children lived at the institution but attended ordinary school in the local community. Some children were sent far from home and spent several years in an institution. In this anthology, we take a close look at several of these institutions: Falstad School and Home, Rostad Home for Children, Røstad School, and Havika Sami Boarding School, all located in the former county of Nord-Trøndelag. In addition, we look at Folåsa, a psychiatric institution for youth in Sweden, and we will learn of the experiences of a group of boys during the Second World War. We also gain insight into the circumstances that gave rise to these institutions through for example the pioneering Norwegian institution Toftes Gave. In addition, we explore the debates that took place at the time as well as contemporary cultural understandings of life at these institutions. The book is aimed at students, professionals and researchers in the fields of child welfare, teacher training and special pedagogy. It will also be of interest to those concerned with the history of education, childhood, the development of welfare society and the local history of the regions where the various institutions were located. Barnehjem og lignende institusjoner ble etablert i Norge i siste del av 1800-tallet. Den nye praksisen med å flytte barn fra sine oppveksthjem til et liv på institusjon var en del av et nytt og omfattende offentlig omsorgs- og ...